Aesthetic and functional results after breast conserving surgery as correlates of quality of life measured by a German version of the Breast Cancer Treatment Outcome Scale (BCTOS) - Heil, Jörg; Holl, Simone Dorothee; Golatta, Michael; Rauch, Geraldine; Rom, Joachim; Marmé, Frederik; Gebauer, Gerhard; Sohn, Christof (The breast, 2010)
This prospective cohort study was carried out to develop a German version of the Breast Cancer Treatment Outcome Scale (BCTOS) and to examine the relations of aesthetic and functional outcome after breast conserving surgery with quality of life (QoL). The study included 189 patients with one-sided, early stage breast cancer. A factor analysis indicated three internally consistent scales of the German BCTOS: Aesthetic Status, Functional Status and Breast Sensitivity Status. QoL was measured by the EORTC Quality of Life Questionnaire C30-BR23 (EORTC). All BCTOS scales were correlated with scales of the EORTC. Correlation magnitudes ranged from 0.24 to 0.67 (p < 0.001). A multiple regression analyses confirmed these results. The analysis of relevant covariates demonstrated that younger patients revealed poorer status on all BCTOS scales. Aesthetic and functional outcome seems to be closely related to quality of Life. The German BCTOS demonstrated to be a useful instrument.
Gesehen am 11.04.2023